Clinical Profile and Laboratory Parameters of Enteric Fever in Children Attending Pediatric OPD in A Tertiary Care Center, Dhaka - Akhtar, Gulshan; Khanam, Afroza; Rahman, Mohammad Abdur; Islam, Quazi Rakibul; Chowdhury, Nurun Nahar (Journal of Shaheed Suhrawardy Medical College, 2022)
Introduction: Enteric fever, a life threatening systemic bacterial infection commonly occurring in developing countries throughout the world. Children suffer the highest burden of this disease among populations in South Asian countries. The clinical presentations are nonspecific, vary in different age group and are often difficult to distinguish clinically from other febrile illness leading to delay in diagnosis, initiation of treatment and ultimately leads to potentially life threatening complications. The aim of our current study was to observe the different pattern of clinical presentation among different age group and laboratory profiles of children presenting with enteric fever. Methodology: This observational type of cross sectional study was carried out at Pediatric outpatient department (OPD) in a tertiary care center, Dhaka, Bangladesh among 80 children during one-year period from March 2019 to February 2020. 1 to 15 years old children diagnosed as enteric fever on the basis of clinical presentation and confirmed by laboratory investigations were enrolled in this study. Results: Total 80 children presenting with fever for ³4 days with strong clinical suspicion of enteric fever followed by laboratory confirmation were included in this study. Children with fever that mimic other febrile illness and those who were already on antibiotic treatment were excluded. We categorized the children in 3 age groups to see the variability of symptoms and signs in different age group. Majority (62.5%) of the study population were school aged children with a male to female ratio of 1.5:1. 68.7% children were from lower class family habituated to drink un boiled supply water (60%) and consumed both homemade and outside foods (66.2%). Fever (100%), anorexia (80-90%), vomiting (30-60%) and coated tongue (70-80%) were consistently present in all age groups. Preschool aged children commonly presented with diarrhea (70%), pallor (60%) and hepatomegaly (70%), whereas abdominal pain (84%), constipation (60%), hepatomegaly (70%) and or splenomegaly (20%) was observed among school aged children. Adolescent group had headache (80%), myalgia (70%) and cough (60%) as their prominent symptoms. Laboratory parameters revealed leukocytosis in 45%, positive Widal test among 62.4% and positive blood culture in 37.5% study group. Conclusion: Enteric fever still remains a serious public health concern in pediatric groups in under developed and developing countries mostly due to substandard drinking water supply, defective sewage system and poor sanitation. Early and accurate diagnosis of this disease followed by initiation of appropriate treatment is crucial in lowering case fatality and also identify carriers those may be responsible for acute outbreak of enteric fever. J Shaheed Suhrawardy Med Coll 2021; 13(1): 50-57